2019
DOI: 10.1371/journal.pone.0215683
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of neonatal sepsis in India: A systematic review and meta-analysis

Abstract: Background The incidence of neonatal sepsis in India is the highest in the world. Evidence regarding its risk factors can guide clinical practice and prevention strategies. Objective To review, assess and synthesize the available literature from India on the risk factors of sepsis among neonates. Methodology A systematic review was conducted. We searched PubMed, CINAHL, Scopus, Web of Science, Popline, IndMed, Indian Science Abstracts and Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
77
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 56 publications
16
77
1
6
Order By: Relevance
“…Premature neonates were at higher risk of neonatal sepsis. This finding is in agreement with the several findings from studies conducted in referral hospitals of Ghana [18], Ethiopia [15] and Tanzania [8]. This could be explained by the fact that premature babies are at a higher risk of infection because of their immature immune system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Premature neonates were at higher risk of neonatal sepsis. This finding is in agreement with the several findings from studies conducted in referral hospitals of Ghana [18], Ethiopia [15] and Tanzania [8]. This could be explained by the fact that premature babies are at a higher risk of infection because of their immature immune system.…”
Section: Discussionsupporting
confidence: 93%
“…Premature rupture of membrane (PROM) [8] [17], history of maternal urinary tract infection (UTI) during pregnancy, gestational age < 37 weeks, Apgar score < 7 at 5 th minute, history of artificial ventilation of the newborn, not crying immediately at birth [15] [18], delay in care seeking, and lack of access to well-trained health workers [10] [19] were identified as major contributing factors of neonatal sepsis. In the African region, lack of adequate resources delays in the diagnosis and prompt treatment of neonatal sepsis, major contributing factor to the high morbidity and mortality rates among the neonates.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that delay in initiation of breastfeeding, having neonatal health problems, neonate's low birth weight, being preterm, and nighttime delivery was identified factors that significantly raise the risk of neonatal hypothermia. Similar findings were also reported from previous meta-analysis studies [39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…The risk factor of sepsis prior to delivery like preterm pre-labour rupture of membranes (pPROM) >24hours, foul smelling liquor, chorioamnionitis, maternal fever was found to be 11% in U.K cohort as compared to signi cant 43.6% (p<0.001) in Indian cohort. This corroborates with a signi cant postnatal blood culture proven sepsis (1.7% v 32.4%) in Indian cohort, it is known from previous studies the increased incidence of sepsis in Indian context [31].…”
Section: Discussionsupporting
confidence: 88%